Early congenital syphilis: Resurgence of an entity nearing elimination - Khushali H Shah; Ashish G Jagati; Santoshdev P Rathod; Raju G Chaudhary (Wolters Kluwer Medknow Publications, 2019)
A 45-day-old female infant was brought to a tertiary care center with the chief complaints of skin lesions over both hands and feet and perianal area since birth. Associated systemic complaints included rhinitis and diarrhea. Clinical examination revealed erosions with moist, erythematous base in an acral distribution, cheilitis, and perianal moist erythematous lesion. Based on the history and clinical examination findings of a congenital bullous rash, acrodermatitis, and periorificial moist lesion, rapid plasma reagin test was advised which came 1:512, thus confirming the diagnosis of congenital syphilis.